2014
DOI: 10.1007/s10461-014-0727-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Safety, Acceptability, and Preliminary Efficacy of Measurement-Based Care Depression Treatment for HIV Patients in Bamenda, Cameroon

Abstract: Background Depression affects 18-30% of HIV-infected patients in Africa and is associated with greater stigma, lower antiretroviral adherence, and faster disease progression. However, the region's health system capacity to effectively identify and treat depression is limited. Task-shifting models may help address this large mental health treatment gap. Methods Measurement-Based Care (MBC) is a task-shifting model in which a Depression Care Manager (DCM) guides a non-psychiatric (e.g., HIV) provider in prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 22 publications
1
55
0
Order By: Relevance
“…Research has demonstrated the effectiveness of collaborative care models to integrate MSD treatment into primary care . While limited, existing research indicates that integrating MSD care into HIV care in LMICs has the potential to improve mental health and HIV treatment outcomes . Additional research on the effectiveness of integrating MSD and HIV care is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated the effectiveness of collaborative care models to integrate MSD treatment into primary care . While limited, existing research indicates that integrating MSD care into HIV care in LMICs has the potential to improve mental health and HIV treatment outcomes . Additional research on the effectiveness of integrating MSD and HIV care is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations include the strict inclusion criteria which excluded non‐English, unpublished studies and computer‐based studies. Although several studies that were carried out subsequent to this review addressed some of these limitations, they were largely pilot studies that utilised non‐random samples or were uncontrolled and all had sample sizes of <100 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of available data from studies conducted before the advent of highly active antiretroviral therapy and of controlled studies that systematically assess efficacy and safety of some classes of psychotropic drugs (e.g., antipsychotic and anxiolytic medications). In particular, overall, there is compelling evidence that the appropriate use of antidepressant medications can improve the quality of life of mentally ill HIV-infected individuals and the adherence to antiretroviral therapy [5, [109][110][111][112]. A recent meta-analysis reviewed 29 studies of the effect of depression treatment on HIV adherence.…”
Section: Treatment Of Depression In Hiv-infected Patientsmentioning
confidence: 99%